The relative contributions of clinical and socio-cultural factors to treatment delay among patients with schizophrenia in south-east Nigeria - Paul Chigozie Odinka, Dr. (International Journal of Psychosocial Rehabilitation, 2015)
The study aimed to determine the relative contributions of clinical and socio-cultural factors to treatment delay among pa- tients with schizophrenia. A cross-sectional study of 360 patients who had no previous contact with psychiatric services. All factors associated with long duration of untreated psychosis (DUP) in univariate analyses at the significant level of p